Medical Financial Hardship Intensity and Financial Sacrifice Associated with Cancer in the United States - Han, Xuesong; Zhao, Jingxuan; Zheng, Zhiyuan; de Moor, Janet S; Virgo, Katherine S; Yabroff, K Robin (Cancer epidemiology, biomarkers & prevention, 2020)
With rising costs of cancer care, this study aims to estimate the prevalence of, and factors associated with, medical financial hardship intensity and financial sacrifices due to cancer in the United States. We identified 963 cancer survivors from the 2016 Medical Expenditures Panel Survey - Experiences with Cancer. Medical financial hardship due to cancer was measured in material (e.g., filed for bankruptcy), psychological (e.g., worry about paying bills and finances), and behavioral (e.g., delaying or forgoing care due to cost) domains. Nonmedical financial sacrifices included changes in spending and use of savings. Multivariable logistic models were used to identify characteristics associated with hardship intensity and sacrifices stratified by age group (18-64 or 65+ years). Among cancer survivors ages 18 to 64 years, 53.6%, 28.4%, and 11.4% reported at least one, two, or all three domains of hardship, respectively. Among survivors ages 65+ years, corresponding percentages were 42.0%, 12.7%, and 4.0%, respectively. Moreover, financial sacrifices due to cancer were more common in survivors ages 18 to 64 years (54.2%) than in survivors 65+ years (38.4%; < 0.001). Factors significantly associated with hardship intensity in multivariable analyses included low income and educational attainment, racial/ethnic minority, comorbidity, lack of private insurance coverage, extended employment change, and recent cancer treatment. Most were also significantly associated with financial sacrifices. Medical financial hardship and financial sacrifices are substantial among cancer survivors in the United States, particularly for younger survivors. Efforts to mitigate financial hardship for cancer survivors are warranted, especially for those at high risk.